Update of Radiofrequency Ablation for Treating Benign and Malignant Thyroid Nodules. The Future Is Now - Tufano, Ralph P.; Pace-Asciak, Pia; Russell, Jonathon O.; Suárez, Carlos; Randolph, Gregory W.; López, Fernando; Shaha, Ashok R.; Mäkitie, Antti; Rodrigo, Juan P.; Kowalski, Luiz Paulo; Zafereo, Mark; Angelos, Peter; et al. (Frontiers in Endocrinology, 2021)
Thermal and chemical ablation are minimally invasive procedures that avoid removal of the thyroid gland and target symptomatic nodules directly. Internationally, Radiofrequency ablation (RFA) is among one of the most widely used thermal ablative techniques, and is gaining traction in North America. Surgery remains the standard of care for most thyroid cancer, and in the right clinical setting, Active Surveillance (AS) can be a reasonable option for low risk disease. Minimally invasive techniques have emerged as an alternative option for patients deemed high risk for surgery, or for those patients who wish to receive a more active treatment approach compared to AS. Herein, we review the literature on the safety and efficacy of RFA for treating benign non-functioning thyroid nodules, autonomously functioning thyroid nodules, primary small low risk thyroid cancer (namely papillary thyroid cancer) as well as recurrent thyroid cancer.